(untitled) (Revista de Investigaciones Universidad del Quindío, 2011)
In this paper, the results of the research project “Representative Analysis of Stories from Gabriel García Márquez National Story Contest (2007)” are contrasted with three important topics: Educational Revolution; which determines the development of Colombian’s educational goals along with guidelines and standards for the Spanish language area, which in turn provides a framework to the educators, and finally a massive evaluation of the education’s competencies (pruebas SABER). This research allows us to compare the gap between the student’s expected scores level and the real results achieved by the students at the time of producing written texts.